PENGEMBANGAN EKSPOR PRODUK KOMPONEN OTOMOTIF BERBAHAN BAKU KARET - Reni K. Arianti (Trade Analysis and Development Agency, Ministry of Trade of Republic of Indonesia, 2009)
The big potential of natural rubber as a raw material of rubber goods industry encourages the Government of Indonesia initiated as rubber goods manufacturers leading the world. Industrial rubber goods in question one is wood-fired industrial rubber automotive components. Results of the study indicate that products automotive components made of rubber from Indonesia have not been developed. This is reflected from (i) the market share of the world's only 0.23; (ii) competitiveness in export markets is still relatively low, (iii) the degree of diversification of products and markets are still relatively low, (iv) export is not sensitive to changes in market share, and (v) a low per capita exports. In addition, automotive components made of rubber from Indonesia had positive prospects on two things, namely, (i) there are 3 excellent products, 5 products a priority, and 3 potential products, and (ii) the performance of export products was generally both Indonesia cabaret venue in the country of Japan, Malaysia, Thailand, Viet nam, the United States and Canada. Indonesia's automotive components industry made of rubber has not got special attention from the Government through policy and its development.